Prevalência de parasitos intestinais em crianças de uma creche pública na cidade de São José do Rio Preto, São Paulo - Rossi, Edna Donizeti Castro (2011)
We present here the frequency of intestinal protozoan and helminth infections in children group (0 to 7 years) and investigate their correlation with diarrhea and sociodemographic characteristics by collecting 100 stool samples from municipal day care center in São José do Rio Preto, State of São Paulo. All specimens were processed according Hoffman-Pons-Janner and Faust parasitological methods. Of the analyzed children we verified a prevalence of intestinal parasitism in 49.0%. The point prevalence of single protozoan infections was 37.0% for Giardia lamblia, for 2.0% Entamoeba coli and 2.0% for Endolimax nana. Only one child presented the associated infections of Ancilostomatidae and G. lamblia. Consumption of food outside of daycare center and home was significantly associated with presence of one or more parasite in stool sample. Significant association was also demonstrated between enteroparasitosis and age. It was observed that G. lamblia and Ancilostoma sp. are more prevalent in children from 1 to 2 years. The results show no significant association between the presence of parasites and diarrhea. Thus, we can observe that intestinal parasites still represent a public health problem in Northeast region of São Paulo State, Brazil, especially among children and in area where the socioeconomic conditions are less favorable.